Techniques for predicting dark web events focused on the delivery of illicit products and ordered crime - Romil Rawat; Olukayode Ayodele Oki; Sakthidasan Sankaran; Hector Florez; Sunday Adeola Ajagbe (Institute of Advanced Engineering and Science, 2023)
Malicious actors, specially trained professionals operating anonymously on the dark web (DW) platform to conduct cyber fraud, illegal drug supply, online kidnapping orders, CryptoLocker induction, contract hacking, terrorist recruitment portals on the online social network (OSN) platform, and financing are always a possibility in the hyperspace. The amount and variety of unlawful actions are increasing, which has prompted law enforcement (LE) agencies to develop efficient prevention tactics. In the current atmosphere of rapidly expanding cybercrime, conventional crime-solving methods are unable to produce results due to their slowness and inefficiency. The methods for accurately predicting crime before it happens